Review of Recycled Asphalt Utilization (Rap) for Road Pavement Recycling - Supoyo Supoyo (International Conference on Coastal and Delta Areas, 2017)
Technological developments and advances in road construction are increasing with the creation of technologies in faster and more efficient road construction. One of the asphalt recycling technologies is the use of Reclaimed Asphalt Pavement (RAP) which is hot hot mixed material from the excavation of cold milling mixed with certain additive materials to improve the quality of asphalt for longer life of asphalt because it is considered faster and to reduce continued damage within a short time after repair. This recycled asphalt mixture research aims to know the value of AIV and APV values of each mixing variation. The percentage of RAP used is 23%, 27%, and 31%. Based on the result of research, it is found that RAP aggregate still fulfill the required physical characteristic ie AIV value equal to 6,6% and APV value equal to 20,4% and minimum type minimum weight 2,5, so tends to be more stable at same condition indicated by the stability value is large and the flow is not too low for the AC-BC mixture, but the gradation of RAP aggregate is not suitable for AC-WC mixed specifications so it needs gradation improvement. Keywords: Reclaimed Asphalt Pavement (RAP), AIV value, APV value, aggregate gradation